2017
DOI: 10.1002/jso.24713
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal extension of lymph node metastasis as a prognostic indicator of recurrence and survival in papillary thyroid carcinoma

Abstract: Macroscopic ENE has a significant adverse impact on recurrence and survival after treatment for PTC. ENE is considered a high risk factor for recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 36 publications
5
27
1
1
Order By: Relevance
“…When considering previous studies (5)(6)(7)9,(22)(23)(24)(25), including a recent meta-analysis (8), it seems clear that the presence of ENE is a significant adverse prognostic factor in thyroid cancer. However, the presence and number of ENEs are closely linked with the number of positive LNs, which makes it difficult to incorporate ENEs into the current riskstratification system.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering previous studies (5)(6)(7)9,(22)(23)(24)(25), including a recent meta-analysis (8), it seems clear that the presence of ENE is a significant adverse prognostic factor in thyroid cancer. However, the presence and number of ENEs are closely linked with the number of positive LNs, which makes it difficult to incorporate ENEs into the current riskstratification system.…”
Section: Figmentioning
confidence: 99%
“…The presence of extranodal extension (ENE), which is a well-known adverse prognostic factor for various cancer types (2)(3)(4), has emerged as an important risk factor for the recurrence of PTC (5)(6)(7)(8). Furthermore, Leboulleux et al suggested that the number of ENEs is associated with an increased risk of recurrence of PTC (9).…”
Section: Introductionmentioning
confidence: 99%
“…Another intriguing proposal concerns the lymph node capsule-sprouting growth of metastases of thyroid carcinoma, which presents a scientifically documented prognostic value (see also Table 1) (20). In particular, the categories pN1a and pN1b have been subdivided into the subcategories pN1a1/pN1b1, when metastases were limited to the affected lymph nodes or pN1a2/pN1b2, when metastases exhibited extranodal spread.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the concept of "minimal extrathyroid spread" of thyroid carcinomas in the context of the special anatomical conditions of the thyroid gland and its limiting structures must be more precisely histomorphologically defined than before (6,(12)(13)(14)(15)(16). Nevertheless, the clinical impact of minimal extrathyroidal extension in patients with papillary thyroid microcarcinoma is still controversial (17)(18)(19)(20).…”
Section: Th Edition Of the Tnm Classification Of Thyroid Carcinomasmentioning
confidence: 99%
“…Roh et al, from Asan Medical Center in Korea reviewed their experience of 2071 patients undergoing thyroidectomy . Forty‐seven percent of these patients had positive nodes, while microscopic extranodal extension was noted in 13% and macroscopic extranodal extension was noted in 3.4% (70 patients).…”
mentioning
confidence: 99%